Rekonsiliasi Konjungtivitis Iritatif (IC) dan Penyakit Mata Kering (DED): Sebuah Tinjauan Literatur untuk Mengajukan Spektrum Penyakit Permukaan Okular Akibat Polusi - Maharani; Trijayanthi Utama, Winda; Virginia Irawati, Nur Ayu; Sutarto, Sutarto (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
The relationship between particulate matter (PM) and ocular surface disease (OSD) is contradictory. Occupational Health and Safety (OHS) literature in Indonesia consistently links high-dose PM10 (dust/smoke) exposure to Irritable Conjunctivitis (IC). Global epidemiological studies tend to focus on PM2.5 and NO2 as the primary causative agents of chronic DED, while ambient PM10 plays a less significant role. The aim of this study was to reconcile this conflicting evidence using a Systematic Literature Review (SLR) method. A total of 42 studies were narratively synthesized and categorized into three lines of evidence: Indonesian occupational exposure (OHS), global ambient exposure (epidemiology), and pathophysiological mechanisms (in vitro/in vivo). The results revealed a "Pollution-Induced OSD Spectrum" with multiple mechanisms. The OHS evidence (Pathway 1) is valid: high-dose PM10 exposure causes acute IC via a physical-mechanical pathway, which directly damages the epithelial barrier through abrasion. Epidemiological evidence (Pathway 2) is also valid: chronic low-dose PM2.5/NO2 exposure causes DED via a chemical-inflammatory pathway, driven by persistent oxidative stress and tear film instability. Mechanistic evidence (Pathway 3) confirms these two distinct pathophysiological pathways. IC and DED are not separate diagnoses in the context of pollution. They represent distinct manifestations (acute/mechanical vs. chronic/inflammatory) within a single disease spectrum, which depends on the type, dose, and duration of pollutant exposure. Keywords: Air Pollution; Particulate Matter; PM10; PM2.5; literature review